Development of agriculture and regulation of product markets of the Republic of Bashkortostan - E. V. Pushnyak; Yu. Ya. Rakhmatullin (Путеводитель предпринимателя)
Food security in Russia seems to be one of the important criteria for guaranteeing the state security of the country in the medium and long–term forecast. In Russia, this process is regulated by the Food Security Doctrine of the Russian Federation, which defines a number of important tasks: their implementation contributes to maintaining food security, regardless of external and internal conditions. The state program of the agro–industrial complex provides for the comprehensive formation of all industries and sub–sectors, as well as areas of activity of the agro–industrial complex, taking into account Russia’s membership in the WTO, as well as participation in the EEC and other regional associations in the economic space of the CIS. The following main objectives of the state program of the republic in the context of agricultural products have been identified: to ensure the implementation of the Doctrine of Food Security of the Russian Federation for production; create favorable conditions for the development of exports of agricultural products in the republic; ensure sustainable development of cattle breeding; increase the efficiency of the agro–industrial complex through the introduction of innovative and high–tech technologies, etc. The article presents the results of a study on the development of agriculture and regulation of the markets of products of the Republic of Bashkortostan in the context of the global financial crisis.